Reacher. Season two [videorecording (DVD)] - Santora, Nick, 1970- (Paramount, 2024)
Reacher Season Two begins when veteran military police investigator Jack Reacher receives a coded message that the members of his former U.S. Army unit are being mysteriously and brutally murdered one by one. Pulled from his drifter lifestyle, Reacher reunites with three of his former teammates turned chosen family to investigate. Together, they begin to connect the dots in a mystery where the stakes get higher at every turn and bring about questions of who has betrayed them and who will die next.